PV array reconfiguration with electrical energy storage system for power system frequency regulation - Zhou, Jun; Liu, Chong; Li, Kun (Frontiers in Energy Research, 2022)
In this work, a novel PV station participating FR technique based on PV array reconfiguration and battery energy storage system (BESS) is put forward. Through the PV array reconfiguration under Partial shading condition, photovoltaic (PV) system can adjust the output power according to the power dispatch instruction. And with the help of BESS, The PV station can achieve continuous power output. Specifically, a joint PV energy storage system model combining profit maximization and power deviation minimization is established. In order to two conflicting goals simultaneously, multi-objective golden eagle optimizer and improved ideal point decision making method are applied. And Lagrange function is given to determine the weight coefficients of each objective more fairly. Two cases are designed and tested. In the high frequency response simulation test, the profit is increased by 8.4% and the power deviation from FR signal is decreased by 19.98%; meanwhile the profit is increased by 10.07% and power deviation is decreased by 67.69% in the low frequency response test. Therefore, the simulation results verify that the proposed method contributes to the frequency response of PV station.